Dampak Literasi Keuangan Dan Inklusi Keuangan Terhadap Keputusan Mahasiswa Dalam Menggunakan Layanan Dan Produk Bank Syariah - Ambrina Rosada (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research aims to see the effect of financial literacy and financial inclusion on student decisions in using Islamic bank products and services. The type of research used in this research is quantitative with data collection techniques used are questionnaires and questionnaires. The method of determining the sample using the slovin formula obtained 30 research respondents. The data analysis technique uses Structural Equation Modeling (SEM) with the help of SPSS. This study shows that financial literacy and financial inclusion variables have a positive and significant impact on student decisions in using Islamic bank products and services. This research is expected to be able to change the mindset of students towards the use of products and services of Islamic banks. Then it is expected that students use Islamic financial services not on the basis of literacy or inclusion but pay attention to the application of sharia.